MOS 2016 study guide for Microsoft Word Expert - Pierce, John 1954- (Pearson Education, Inc., 2017)
Demonstrate your expertise with Microsoft Word! Designed to help you practice and prepare for Microsoft Office Specialist (MOS).
"Published with the authorization of Microsoft Corporation by: Pearson Education, Inc."--Title page verso. - Includes index. - Print version record
Keywords: Microsoft Word -- Study guides -- Examinations; Electronic data processing personnel -- Certification; Microsoft software -- Study guides -- Examinations; Microsoft Word; Logiciels Microsoft; Examens; Guides de l'étudiant; COMPUTERS; Desktop Applications; Word Processing; Electronic data processing personnel; Certification; Examinations; Microsoft software; Examinations; Study guides